Caminhos da docência que se entrecruzam e se revelam no processo de formação continuada com os docentes do PROEJA FIC - Montagner, Silvia Regina (2013)
This research sets up a study with teachers in continuing education, that participate in the National Program for the Integration of Vocational Education in Basic Education in the Mode of Youth and Adult Education and Continuing and Initial Education - PROEJA FIC, with a view to rebuilding their walks as reflective practitioners and transformers of their own practice. Under this approach, this research aimed to investigate the ways of teaching trajectory in times of continuing education, and the narratives used auto / trans / formative devices as research training with teachers working in PROEJA FIC. Given this, it is proposed a qualitative approach to the research participant interfaces with intersections in the process of research training and professional development, which were systematized in a reflective diary and records of the speeches, the understanding of the analysis Bardin (2004) in order to examine the ways in which teaching trajectory that can be significant and present in the narratives about the self / trans / formation in search of Being More. The co-authors of the research which I dialogued with were 8 teachers, 4 of the municipal education Tupanciretã and 4 from The Federal Institute of Farroupilha Campus Julius Castilhos. The research sought to supply the narrative in the continuing education and sought to establish a dialogue with numerous references to be sensitive teacher, that permeate the work, which aims to contribute to the analysis of the movements in training and career paths as a way of teaching (re) construction. Thus, pointed to an emancipating potential by looking on ourselves, on teaching, life and profession of the teacher, especially when constructed the dialogue and reflective problem-solving for continuing education, as was the case of PROEJA FIC.